Is this simplified?(adsbygoogle = window.adsbygoogle || []).push({});

Use the power rule and the summation rule to find f ' (x) and simplify where possible

f(x) = ((2x^3)/5) - x^2 +3/8

f ' (x) = d/dt(((2x^3)/5) - x^2 +3/8) = ((6x^2)/5) - 2x

Is this the right answer?

**Physics Forums - The Fusion of Science and Community**

# Power & Summation Rules

Have something to add?

- Similar discussions for: Power & Summation Rules

Loading...

**Physics Forums - The Fusion of Science and Community**